General hospital care for people with intellectual disabilities. Issue 1 (4th January 2016) - Glover, Gyles; Fox, Sebastian; Hatton, Chris
Abstract : Purpose: – The purpose of this paper is to explore the extent of compliance of commissioners and providers of hospital services in England with their duty under equalities legislation to be aware of patients with intellectual disabilities as a first step to making appropriate provision for their consequent specific needs. Design/methodology/approach: – National survey of healthcare commissioners undertaken as part of an annual learning disabilities services audit. Findings: – In total, 41.4 per cent of local areas were unable to supply information about numbers of people with intellectual disabilities among those admitted to hospital, 46.7 and 48 per cent, respectively, could not supply this information about out-patient and accident and emergency department attenders. Figures supplied by those able to provide data varied very substantially and overall were so low as to suggest considerable numbers had been missed. Research limitations/implications: – The study is testing what local health commissioners are able to find out from hospitals. The authors do not know the accuracy of the data they reported. Practical implications: – The study suggests approaching half of healthcare commissioners in England have little or no information about the extent of proper adjustment of hospital care for people with intellectual disability in their area. Their responsibility to assure this has been repeatedly asserted by government. Social implications: – The study indicates a need for more work to improve hospital care for people with intellectual disabilities. Originality/value: – This was a government sponsored national study to which local healthcare commissioners were expected to contribute.